Variability of quackgrass (Agripyron repens) biotypes in Québec - Tardif, F.J.; Leroux, G.D. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1991)
Field experiments were conducted in 1985 and 1986 at Sainte-Foy, Quebec, Canada, to characterize the growth variability of 10 quackgrass (Agropyron repens) biotypes collected in Quebec. The growth variables and the pattern of biomass allocation differed significantly among biotypes. Three-fold difference existed among biotypes for the number of tillers and spikes. The number of daughter-shoots varied from 6 to 51. More than 1900 rhizome buds were formed by the most productive biotypes and fewer than 500 by the least productive ones. Biomass varied from 73 to 241 g dry weight between the least and the most productive biotype. The percentage of total biomass allocated to the mother-shoot and the daughter-shoots varied more between years and among biotypes than the percentage allocated to the rhizomes. Reproduction in quackgrass is predominantly vegetative and sexual reproduction is more variable among biotypes and years.